Optimalisasi Manajemen Persediaan Bahan Baku Pada Usaha Pabrik Mie Sinar Mandiri Kabupaten Tana Toraja - Elpasira Nirma; Marinus Ronal; Marchelin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted to find out and analyze how raw material inventory management at the Sinar Mandiri Noodle Factory Business uses the Minimum-Maxsimum method. The method used in this research is a quantitative descriptive method. The results of this research show that using the Min-Max method is more optimal than the method applied by the Sinar Mandiri Noodle Factory Business. By using the Min-Max method, you can save raw material inventory costs in 2023 amounting to IDR 6.687.111..-. Based on these results, the Sinar Mandiri Noodle Factory Business should use the Min-Max method so that raw material inventory management can be more optimal and inventory costs can be minimized so that company profits can be maximized.